IMPLICATURE ANALYSIS IN THE DESPICABLE ME 4 (2024) MOVIE - Purba, Gabriella Gracia Delvara; Silalahi, Charles Marudut; Lim, Felicia (Cahaya Ilmu Bangsa Institute, 2025)
This article offers an examination of implicature in the animated feature “Despicable Me 4” (2024), emphasizing how characters communicate meanings that extend beyond the straightforward interpretation of their spoken lines. Employing H.P. Grice’s framework of conversational implicature, the study explores various examples of implicature throughout the film, illustrating how humor, sarcasm, and social interactions are conveyed through indirect means. By scrutinizing pivotal scenes and character exchanges, the research categorizes the types of implicatures utilized, such as generalized and particularized implicatures, and evaluates their influence on character development and the progression of the plot. The results indicate that implicature significantly enhances the film’s comedic aspects and emotional resonance, enriching the overall narrative experience. This analysis not only highlights the critical role of implicature in animated storytelling but also sheds light on the linguistic techniques employed by the filmmakers to captivate audiences across different age groups. From the research, the writers focus on examining 2 types of implicature and get the results of implicaturec data as much as 21 data. Here are the data, 13 conversational implicature and 8 conventional implicature data.